CAREER PLATEAUING AND IT’S RELATIONSHIP WITH SECONDARY SCHOOL TEACHERS’ PURSUIT OF POST-GRADUATE STUDIES IN NYANDARUA AND MURANG’A COUNTIES, KENYA - Wangechi HSC, Dr. Gaturu Mary; Njuguna, Dr. Felista; Ogeta, Dr. Norbert (Journal of Education and Practice, 2019)
Purpose: Teachers in Kenya exhibit signs of career plateauing, and are registering for post-graduate courses in large numbers. This study investigated whether teachers' pursuit of post-graduate studies is a result of career plateauing. The purpose of the study was to determine the relationship between career plateauing and secondary school teachers' pursuit of post-graduate studies in Nyandarua and Murang'a counties, Kenya. The objectives of the study were to: determine types and levels of career plateauing experienced by secondary school teachers of public schools in Nyandarua and Murang'a Counties; determine the relationship between career plateauing and teachers' decisions to pursue various Post-Graduate courses; and find out whether the structural or job content type of career plateau predicts teachers' decisions to pursue various Post-Graduate courses among secondary schools teachers in public schools in Kenya. Methodology: The study employed the correlational research design. The target population of the study comprised of all the 5,022 teachers (3,581 in Murang'a County and 1,441 in Nyandarua County) in all the public schools in Nyandarua and Murang'a Counties except those which were used in the pilot. From this population, the sample size for each county was computed using the sample size computation formula by Krejcie & Morgan (Cohen, Manion & and Morrison, 2007), which gave 304 teachers from Nyandarua County and 348 teachers in Murang'a County. Stratified random sampling was used to select 304 teachers from Nyandarua County and 348 teachers from Murang'a County giving a total of 652 teachers. In Nyandarua County, the sample size was 152 male and 152 female teachers, while in Murang'a County there was 174 male and 174 female teachers. A questionnaire designed for teachers was used as the main tool for data collection. The study generated quantitative data, which was analyzed using descriptive and inferential statistics. Qualitative data was reported according to themes and involved the use of frequencies and percentages. Linear progression and Analysis of Variance were also used. Results: Decisions to pursue post-graduate studies is expected to increase 0.014 when structural plateauing rises by one and decrease by 0.012 when job content plateauing goes up by one. Both structural and job content plateauing were found to predict decisions to pursue post-graduate studies significantly at p<0.05. Contributions to theory, policy and practice: The Teachers Service Commission should develop a clear road map for career advancement of the teachers to reduce career plateauing. The Teachers Service Commission in collaboration with the ministry of education should design a skills upgrade for teachers through capacity development programmes which should be a requirement for those joining the profession and which should form a basis for promotion